Makna Teologis Kekudusan Allah Pada Peristiwa Kematian Uza Menurut 2 Samuel 6:6-7 - Mandin Weya; Benaya Setia Adhi (Sekolah Tinggi Teologi Kalimantan, 2022)
The doctrine of the holiness of God in the Old Testament is a theological teaching that is difficult for Christians today to understand. The concept of God's holiness is carried out so rigidly that it ignores the human element. In fact, not a few Bible scholars consider that the concept of God's holiness in the Old Testament is contrary to God's love. One of the narratives that record this event is the death of Uza. Uzzah's death in 2 Samuel 6:6-7 is a controversial death. Not many scholars highlight the event according to Old Testament theology as a whole. In fact, some interpreters ignore the unity of the narrative of the Old Testament historical books so that only ethical interpretations are formed. Narrative recording of Uza's death is recorded with the special motives of the narrator. This study uses a literature study, namely by conducting a study of the literature relevant to the research topic. In addition, this study also considers the large structure and theological motifs used by the narrator. The writer of the book of Samuel noticed an important aspect in Leviticus concerning the holiness of God. The incident of Uza's death cannot be studied with an ethical approach, but must look at the intertextual relationship with the book of Leviticus. Finally, the reader can understand that the theology of God's holiness is emphasized more than ethics in the event of Uzzah's death.Doktrin tentang kekudusan Allah dalam Perjanjian Lama merupakan ajaran teologis yang sulit dimengerti oleh orang Kristen masa kini. Konsep kekudusan Allah dijalankan dengan sangat kaku sehingga mengabaikan unsur kemanusiaan. Bahkan, tidak sedikit para sarjana Alkitab menilai bahwa konsep kekudusan Allah dalam Perjanjian Lama bertentangan dengan kasih Allah. Salah satu narasi yang mencatatkan peristiwa itu adalah kematian Uza. Kematian Uza dalam kitab 2 Samuel 6:6-7 merupakan kematian yang kontroversial. Tidak banyak sarjana yang menyoroti peristiwa itu sesuai dengan teologi Perjanjian Lama secara keseluruhan. Bahkan, beberapa penafsir mengabaikan kesatuan narasi kitab sejarah Perjanjian Lama sehingga hanya terbentuk tafsiran yang bersifat etis. Pencatatan narasi tentang kematian Uza dicatatkan dengan motif khusus dari naratornya. Penelitian ini menggunakan studi kepustakaan, yaitu dengan melakukan studi terhadap literatur yang relevan dengan topik penelitian. Selain itu, penelitian ini juga mempertimbangkan struktur besar dan motif teologis yang dipakai oleh narrator. Penulis kitab Samuel memperhatikan aspek penting dalam kitab Imamat tentang kekudusan Allah. Peristiwa kematian Uza tidak dapat dikaji dengan pendekatan etis, melainkan harus melihat hubungan intertekstual dengan kitab Imamat. Akhirnya, pembaca dapat memahami bahwa teologi kekudusan Allah lebih ditonjolkan dari pada etika dalam peristiwa kematian Uza.